Preparo, caracterização e aplicação de compósitos Fe(0)-óxidos de ferro em processos redutivos para remediação ambiental. - Flavia dos Santos Coelho (2008)
The reduction of Cr(VI) in aqueous medium with Fe(0)/Fe3O4 composites was investigated in bench procedures scale, particularly focusing on the efficiency of its fundamental chemical processes. The obtained results reveal that the combination of manually ground Fe(0) and Fe3O4 renders a very active system on reducing Cr(VI). The chemical characterization of these composites with Mössbauer and X-ray excited photoelectrons spectroscopies and scanning electron microscopy analyses indicates that, after grinding, the two starting solids are distributed in such a way that a Fe3O4 layer coats the Fe(0) particles.The higher chemical reducing efficiency of composites, relatively to solelymetallic iron or magnetite, can be explained by a model involving the formation of chemical species that are significantly more active, on the surface of the system Fe(0)/Fe3O4. According to this model, the higher activity of the system Fe(0)/Fe3O4 would be related to the reducing process of Fe3+, formed during the reduction of Cr(VI), via the electron transfer from Fe(0) to the surface Fe3+, regenerating Fe2+, which is active on the process. The Cr(VI) reduction reaction does occur basically on the heterogeneous phase, being favored in low pH medium, below the zero-point charge of magnetite, in a condition that the composite surface is positively charged and the electrostatic attraction of chromate contributes to increase the reaction rate. The whole process of Cr(VI)reducing leads to the increase of pH due to H+ consumption, with a progressive lowering of the reaction rate. However, the activity of the system Fe(0)/Fe3O4 can be regenerated by increasing the medium acidity. The composite can be, then, reused several times. The reduction of Cr(VI) in aqueous medium by the Fe(0)/Fe3O4 system leads to the formation of insoluble Cr(III) compounds on the surface of the composite, which favors the remediation mechanisms of the environment, taking into account that the Cr(III) species tend to be much less toxic.